Antioxidant activity of polyphenolic extracts of filamentous fungus Mucor circinelloides (WJ11): Extraction, characterization and storage stability of food emulsions. (April 2020) - Hameed, Ahsan; Hussain, Syed Ammar; Ijaz, Muhammad Umair; Ullah, Samee; Muhammad, Zafarullah; Suleria, Hafiz Ansar Rasul; Song, Yuanda
Abstract: Optimized extraction of antioxidants from Mucor circinelloides WJ11 (MCWJ11) biomass was studied. Storage, stability, composition and antioxidant properties in model food emulsion systems were also investigated. Both the extraction approach and solvent type were found to significantly (p<0.05) influence the recovery yield of antioxidants and their antioxidant capacity. The 90% aqueous binary solvent system with semi-polar solvents (i.e., acetone and ethanol) showed increased recovery levels of TPC, TFC and TCT, with the highest antioxidant bioactivity obtained using a pressurized liquid extraction. Ninety-day storage studies of microbial ethanolic extracts with accelerated storage/processing showed increased degradation of antioxidants at elevated temperatures (22–28 o C), with a negligible influence of white light. Substantial loss of microbial polyphenolic compounds was also observed, especially in fetal bovine serum at 37 °C with a 48 h stability test in biologically relevant buffers. Liquid–liquid fractionation of microbial ethanolic extracts led to the most active antioxidative fractions with ethyl acetate and 1-butanol. Comparatively, EtAc had better antioxidative activity (in a dose-dependent manner) against lipid oxidation in the tested food model emulsion systems. Furthermore, metabolic fingerprinting of the ethanolic extracts showed that the secondary metabolites of MCWJ11 were alkaloids, pigments, benzoic acids, terpenoids, cinnamic acids, benzopyrans, aspalathins and phloretins.